Resisting the Pressures of Academia: The Importance of Including Care in Doctoral Study - Carol Rogers-Shaw; Davin Carr-Chellman (Adult Education Research Conference, 2018)
This study examines the effects of caring relationships in doctoral study. An exploration of the experiences of first year female students showed care facilitated learning.
Keywords: doctoral study; socio-emotional learning; care; first year female students; feminist research